Money Supply, Inflation, and Economic Growth Nexus in Nepal: Evidence from VECM - Shrestha , Jamuna; Adhikari, Gyan Mani; Parajuli, Devendra; Sapkota, Nabin (Academia Journal of Research and Innovation, 2026)
The current study examines how money supply, inflation, and economic growth relate to each other in the long run in Nepal using a Vector Error Correction Model (VECM) that covers the 1995–2022 time horizon. Logarithmic transformation of annual indicators of real gross domestic product (GDP), broad money supply (M2), and consumer price index-determined rates of inflation are calculated. The cointegration test by Johansen shows the presence of long term equilibrium relationships between the variables. The estimation of VECM depicts that money supply has a positive impact on economic growth in the long term, but inflation has a negative impact. The error-correction term suggests that the recovery of short-run disequilibrium is about 32.4 7 percent per year. The Granger causality tests indicate that money supply and economic growth have bidirectional and inflation has a unidirectional relationship. These empirical results have great implications in the design of monetary policy in Nepal, indicating that modest monetary growth can stimulate growth, whereas extreme inflation will be counterproductive to economic growth.